English Learning Innovation at Al-Yasini Integrated Islamic Boarding School Pasuruan: Qualitative Method - Dewi Masitah (Darussalam English Journal (DEJ), 2021)
Pesantren is an Islamic educational institution that has existed in Indonesia for hundreds of years, but its existence has been challenged by the presence of colonialists, secularists, and the challenges of globalization and the community's need for education is increasingly complex. How pesantren take strategic steps to answer these challenges. So from here the researchers are interested in conducting research on English learning innovations at the Al-Yasini Integrated Islamic Boarding School with the following problem formulation. Second, how is the development of English learning at the Al-Yasini Integrated Islamic Boarding School? This study uses a sociological approach of education and this type of research uses qualitative phenomenology. The results of this study indicate that 1) The development of English learning is based on the thoughts of the caregivers of the Al-Yasini Integrated Islamic Boarding School to meet the educational needs of the community and the obligation of students to spread Islam throughout the world. In delivering da'wah not everyone understands Arabic, so da'wah can use English as an international language. 2) Mastering English and being able to communicate is considered important in da'wah, so it must be developed by means of developing English so that students can convey Islamic messages to all levels of the world community according to the profession of each student.